2017
DOI: 10.1080/19390211.2017.1329244
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Biosynthesis, Analytical Techniques, and Pharmacological Activities of Trigonelline as a Plant Alkaloid

Abstract: Trigonelline (TRG) as a polar hydrophilic alkaloid is extracted from many plant species, for example, Trigonella foenum-graecum, Allium sepapea, Coffea sp, Pissum sativum, Glycine max, and Lycopersicon esculentum. Numerous biological activities have been reported for TRG such as protection of heart and liver and treatment of hyperglycemia, hypercholesterolemia, nervous and hormonal disorders, and cancers. Thus, the aim of this review is to summarize some information about TRG's biosynthesis pathway, pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 72 publications
3
50
0
3
Order By: Relevance
“…Furthermore, many common foods contain TGN such as barley, cantaloupes, corn, onions, soybeans, peas, and tomatoes 4 . Numerous reports on the biological activity of TGN have mentioned its role in protecting the liver and heart and in the treatment of hypercholesterolaemia, hyperglycaemia, and central nervous system disorders 5 . Only one report has suggested the potential role of TGN as an anti-Alzheimer’s drug.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many common foods contain TGN such as barley, cantaloupes, corn, onions, soybeans, peas, and tomatoes 4 . Numerous reports on the biological activity of TGN have mentioned its role in protecting the liver and heart and in the treatment of hypercholesterolaemia, hyperglycaemia, and central nervous system disorders 5 . Only one report has suggested the potential role of TGN as an anti-Alzheimer’s drug.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have been selected because they are among the most attractive active molecules contained in the SCG for cosmetic purposes. In particular, caffeic acid is very well known as an antioxidant with free radical scavenging properties [16], while trigonelline is beneficial for its antimicrobial properties, and thus it could aid in preventing the microbial contamination of the extracts and cosmetic formulations [17]. Niacinamide possesses a stabilizing effect on epidermal barrier function, reducing the trans epidermal water loss and thus favoring the skin hydration.…”
Section: Introductionmentioning
confidence: 99%
“…With an HPLC-florescence detector, aspartic acid has been found to be the main content along with arginine as a minor content. Trigonelline performs many biological activities that affect the brain, including but not limited to antinociception, the stimulation of dopamine release, and inhibition of the γ-aminobutyric acid (GABA) receptor response [ 37 ]. In addition, previous studies revealed that DL also contains amino acids such as arginine and aspartic acid [ 38 ].…”
Section: Discussionmentioning
confidence: 99%